2018
DOI: 10.5539/ies.v11n7p179
|View full text |Cite
|
Sign up to set email alerts
|

Counsellor Trainees’ Views about Practicum Exercises in the Guidance and Counselling Programme of the Delta State University, Abraka, Nigeria

Abstract: The study investigated counsellor trainees' views of practicum exercise in Guidance and Counselling programme in Delta State University, Abraka, Nigeria. To guide the study, four research questions were raised and one hypothesis formulated. The study is a descriptive survey which utilized the ex-post facto design. The population was made up of all guidance and counselling students who had done the practicum exercise in the 2017 Sandwich contact. A sample of 35 students was used and this was drawn using purposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…These studies demonstrated that there is no significant or moderating effect of gender on students' scholarly performance. Moreover, this finding is at variance with the studies of Akpochafo (2001), Adeyemi and Ajibade (2020) and Yousaf et al (2012), which submitted male dominance in scholarly performance as male students out performed their female counterparts in the studies.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…These studies demonstrated that there is no significant or moderating effect of gender on students' scholarly performance. Moreover, this finding is at variance with the studies of Akpochafo (2001), Adeyemi and Ajibade (2020) and Yousaf et al (2012), which submitted male dominance in scholarly performance as male students out performed their female counterparts in the studies.…”
Section: Discussioncontrasting
confidence: 68%
“…Okereke (2011) and Awodun and Oyenini (2018) submitted similar findings. However, Akpochafo (2001), Adeyemi and Ajibade (2020) and Yousaf et al (2012) reported a contrary finding where the study discovered significant effect of gender on the scholarly performance of male and female students in social studies. Whether the biological construct of gender will impact the scholarly performance of junior secondary school students in social studies or not was also determined by this study.…”
Section: Agjsrmentioning
confidence: 93%